Sleepiness as a Local Phenomenon - D’Ambrosio, Sasha; Castelnovo, Anna; Guglielmi, Ottavia; Nobili, Lino; Sarasso, Simone; Garbarino, Sergio (Frontiers in Neuroscience, 2019)
Sleep occupies a third of our life and is a primary need for all animal species carefully studied so far. Sleep loss has detrimental effects on general health, cognition, and emotions. It is common experience that sleep loss is associated with the subjective feeling of sleepiness and decreased performance. Nonetheless, chronic sleep restriction and subsequent excessive daytime sleepiness are getting large-scale problems in developed countries. The idea that small brain areas can be asleep while the rest of the brain is awake and that local sleep may account for at least some of the cognitive and behavioral manifestations of sleepiness is making its way in the scientific community. We herein clarify the different ways sleep can intrude into wakefulness, summarize the main findings on this “hot-topic”, highlight its negative effects on human health, and offer speculative hypotheses that may account for local aspects of sleep and sleepiness.